WHY IS IT IMPORTANT TO LEARN ENGLISH? - Durova , Shakhnoza Shokirovna (Educational Research in Universal Sciences, 2023)
This article discusses the importance of learning English in human’s life. In today’s non- stop developing world, a great deal of attention is being paid on learning languages.